(untitled) (Bangladesh Journal of Genetics and Biotechnology, 2007)
Key words: Selection; G x E models; regression coefficient and deviation mean square; Capsicum annum Bangladesh j. genet. biotechnol. 5 (1&2): 9-13, 2004 (June & December)